Redescription of Pionosyllis procera (Polychaeta: Syllidae), with comments on its reproduction and systematic position - San Martín, Guillermo; Estapé, Sonia (Revista de Biología Tropical, 1993)
Several specimens of Pionosyllis procera Hartman, 1965 (Syllidae), previously known only from an incomplete original description, were collected near Cuba. This species does not reproduce by epigamy, the typical condition in Eusyllinae, but rather by sexual stolons. Both male and female stolons are produced by schizogarníc scissiparity, a reproductive method previously reponed for Syllinae. The systematic position of this species is problematic, as it presents many morphological characters typical of Eusyllinae as well as a few of Syllinae. This paper redescribes Pionosyllis procera, and describes its stolons for the first time.